The Effect of Environmental Awareness, Sustainable Corporate Image, and Green Product Price on Consumer Purchase Intention in Indonesia - Ellyany Sinaga, Hommy Dorthy; Fenny, Fenny; Nainggolan, Elisabeth; Januarty, Widalicin (West Science Social and Humanities Studies, 2024)
This quantitative study examines the relationship between customer purchase intention in Indonesia and environmental awareness, sustainable company image, and green product costs. Likert scale items were used to measure the dimensions in a survey with 279 Indonesian consumers as a sample. Regression analysis was performed on the data using SPSS version 26. The findings showed a strong positive correlation between customer purchase intention, green product price, sustainable company image, and environmental awareness. In particular, customer purchase intention was positively influenced by more environmental awareness and good opinions of business sustainability. Furthermore, Indonesian customers showed a readiness to pay more for environmentally friendly goods. Businesses and legislators seeking to encourage sustainability and ecologically conscious customer behavior in Indonesia should take note of these findings.